PERAN GURU PAI DALAM MEMBENTUK KARAKTER PESERTA DIDIK SDN 050776 TANJUNG PASIR - Halimatun Sa'diah (Journal of Community Devation, 2025)
Educate students to become intelligent human beings and also develop their personalities to have noble character. Therefore, character education is certainly important for all levels, namely from elementary school to university. In general, character education starts from an early age, if a person's character has been formed from an early age, then when they grow up they will not easily change even if temptation or seduction comes very tempting. By providing character education from an early age, it is hoped that we can produce excellent alumni, namely children of the nation who are faithful, devout, have noble character, have expertise in their fields and have character. Based on the results of observations at SD Negeri 050776 Tanjung Pasir, Prabumulih City, there are still many students who are not optimal, therefore it can be seen the description of the character of the students of SD Negeri 050776 Tanjung Pasir, therefore researchers are interested in researching the "Role of Religious Education Teachers." Islam in Shaping the Character of Students at SD Negeri 050776 Tanjung Pasir. Focus This research is about the role of Islamic Religious Education teachers in shaping the character of students at SD Negeri 050776 Tanjung Pasir. This research uses qualitative research which leads to an evaluation process of research objects to obtain the necessary data, so the author uses several data collection methods, namely observation, interviews and documentation methods. As for implementing the character formation of students at SD Negeri 050776 Tanjung Pasir, Prabumulih City, PAI teachers are greatly helped by the SOPs created by the school, including: first, namely the superior curriculum aspect of SD Negeri 050776 Tanjung Pasir, Prabumulih City which is applied in the subject, tawhid which is code or characteristics that contain the personality that students at SD Negeri 050776 Tanjung Pasir Kota must have Prabumulih, the third is EA (Excel Appreciation), namely points given to students and are a consequence of students' actions that violate school rules by deducting points every time they violate. From the things above, it will be very easy for PAI teachers to shape the character of students so that they become individuals with character and achieve the goals and expected results.